P152 The National Lung Cancer Audit: year 6 completeness and outcomes. (2nd December 2011) - Beckett, P; Woolhouse, I; Stanley, R; Yelland, A; Peake, M D
Abstract : Introduction: The National Lung Cancer Audit is run jointly by the Royal College of Physicians and The Information Centre for health and social care, and is commissioned by the Healthcare Quality Improvement Partnership (HQIP). Its development was driven by the realisation that lung cancer outcomes vary widely across the UK and are poor compared to other western countries. The aim of the audit is to facilitate service improvement by recording elements of process and outcomes in lung cancer on a large scale and, using case-mix adjustment, to explain the wide variations noted and improve standards of care. Although several other countries also submit data to the audit, this abstract presents provisional results for England only. Results: In Year 6, participation has again increased and all trusts have now contributed data at some time. Completeness of data on individual cases remains high although it is noteworthy that 18% of cases are submitted without a disease stage and 16% without performance status. This year the results show that the histological confirmation rate has risen substantially to nearly 77%, and 96% of patients have been discussed in an MDT, although the surgical resection and anti-cancer treatment rates have not increased further. Conclusions: Participation remains high and the audit continues to collect data on close to 100% of cases of lung cancer and mesothelioma that present to secondary care. Overall treatment rates seem to have stopped improving, although it is acknowledged that some of the earlier annual improvements reflected improvements in data quality. The rise in HCR is likely to reflect a real change in practice, possibly due to the new found importance of tissue (choice of chemotherapy, use of EGFR antagonists) and possibly due to the focus given to HCR by the audit itself. It is of concern that a significant minority of patients appear to be managed without information on disease stage and PS—key variables needed for appropriate management of patients.